Developing leaders as symbolic violence: Reproducing public service leadership through the (misrecognized) development of leaders' capitals. Issue 1 (February 2013) - Tomlinson, Michael; O'Reilly, Dermot; Wallace, Mike
A critical analysis is developed of the part that centrally initiated leadership development plays as a strategic lever for ensuring a steady supply of organizational leaders equipped and willing to meet the goals of widespread service improvement. Selected Bourdieusian conceptual tools are employed to illustrate how centrally initiated development of leaders operates as a form of 'symbolic violence': a covert means of perpetuating political elite domination. Organizational leaders misrecognize it as promoting their interest in expanding their influence because they are attracted by the opportunity it overtly offers to build their 'capitals'. This process operates across two main administrative levels: the central (system) level and the organizational (local) level. The analysis is empirically grounded through the case of UK public services, drawing on a study of public service leaders, policymakers and representatives from national leadership development bodies in the United Kingdom. The findings illustrate how central policy elites endeavour to use leadership development to acculturate organizational leaders capable of responding favourably to a reconfigured and re-professionalized public service field. At the same time, organizational leaders consent to this through its perceived value in expanding their influence and developing their leader-related forms of capital.